Co-Colonization of Non-difficile Clostridial Species in Antibiotic-Associated Diarrhea Caused by Clostridioides difficile - Daniel Salas-Treviño; Samantha Flores-Treviño; Carlos Cisneros-Rendón; Cristian Valdemar Domínguez-Rivera; Adrián Camacho-Ortiz (Antibiotics)
Background/Objectives: Antibiotic-associated diarrhea (AAD) is a public health problem that develops in the hospital setting. The most common causative agent of AAD is Clostridioides difficile infection (CDI), although other non-difficile Clostridia (NDC) might also be present. NDC include members of the RIC group such as Clostridium ramosum [T. ramosa], Clostridium innocuum and Clostridium clostridioforme [E. clostridioformis]. The co-colonization of NDC and CDI in patients with AAD has not been fully analyzed. Methods: We compared clinical and laboratory data of patients with C. difficile infection (CDI) plus NDC against patients with only CDI. This study was a retrospective, case–control study. Hospitalized confirmed CDI cases were analyzed. CDI detection was performed using a 2-step diagnostic algorithm, including glutamate dehydrogenase (GDH) with toxin A/toxin B assays and molecular detection of the tpi gene. Stool samples were cultured and colonies morphologically compatible with any Clostridia were identified with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Fisher’s exact test and odds ratio (OR) were calculated to determine the degree of correlation between the variables and the study groups. Results: In the CDI + NDC group (n = 7), positive culture was observed for C. ramosum [T. ramosa] (n = 3), C. innocuum (n = 3), and C. butyricum (n = 1). According to our results, CDI + NDC patients received more days of antibiotic therapy, took more days to reduce diarrhea, had a significant increase in the number of days to suppress diarrhea, and previous hospitalizations were more frequently reported. Conclusions: In conclusion, the positive culture of NDC species such as C. innocuum or C. ramosum in patients with AAD caused by CDI correlates with treatment extension and/or failure.